Fluorescence optical imaging and 3T-MRI for detection of synovitis in patients with rheumatoid arthritis in comparison to a composite standard of reference. Issue 90 (May 2017) - Thuermel, Klaus; Neumann, Jan; Jungmann, Pia M.; Schäffeler, Christoph; Waldt, Simone; Heinze, Alexander; Beckmann, Alexander; Hauser, Christine; Hasenau, Anna-Lena; Wildgruber, Moritz; Clotten, Sigrun; Sievert, Matti; et al.
Abstract: Objectives: To address whether Indocyanine Green (ICG) enhanced fluorescence optical imaging (FOI) is more sensitive than magnetic resonance imaging (MRI) in the detection of synovitis of the wrist and finger joints in rheumatoid arthritis and to analyze the performance of FOI depending on the grade of synovitis. Methods: Twenty patients with highly active rheumatoid arthritis (mean DAS28-ESR 5.25 ± 1.0) and thirteen healthy volunteers underwent clinical examination, FOI and contrast-enhanced 3T-MRI. Joints were rated by three independent readers semiquantitatively (grade 0–3: no, low, moderate and high grade synovitis) and compared to a semiquantitative composite standard of reference (cSOR, grade 0–3) that incorporated clinical parameters, FOI and MRI results. Results: 2.868 evaluations in 956 joints were performed. FOI had an overall sensitivity of 57.3% and a specificity of 92.1%, whereas MRI had a sensitivity of 89.2% and a specificity of 92.6%. The sensitivity of FOI increased with the degree of synovitis to 65.0% for moderate and severe synovitis (specificity 88.1%) and 76, 3% for severe synovitis (specificity 80.5%). The performance of FOI decreased with the degree of synovitis with false negative results predominantly for mild (156/343, 45.5%) and moderate (160/343, 46.6%) synovitis and false positive FOI evaluations predominantly based on weak (grade 1) signals (133/163, 81, 6%). Conclusion: FOI has a lower sensitivity than 3T-MRI in the detection of synovitis of the hand and finger joints. The diagnostic performance of FOI decreases with the degree of synovitis and with the strength of FOI signals.